Analisis Kepribadian Tokoh Utama dalam Novel Neraka Dunia Karya Nur Sutan Iskandar - Alfi Nurcahyo; Rita Arianti; Hermawan Hermawan (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2021)
The purpose of this study was to describe the main character in the novel Hell of the World by Sutan Nur Iskandar. This research method is descriptive with the type of qualitative research. The results show that the dominant main character has a personality that is influenced by the Id element, this is because the main character Ahmad Salam instinctively determines his personality to have a strong stance, not easily influenced by others and has an independent spirit in life. No. Id plays a more important role in every action and behavior that the main character takes because these actions come from the impulse of desire in himself without being influenced by others. In conclusion, the personality elements of the characters contained in the novel Hell of the World by Sutan Nur Iskandar are of 3 types, namely, 1) the id element contains eleven data, 2) the ego element contains ten data, 3) the super ego element contains eight data. Keywords: World Hell, Novel, Personality Uncertainty